Assessing the Viability of Translocated Mongolian Dung Beetles (Gymnopleurus mopsus) for Ecological Restoration in Republic of Korea: An Analysis of Environmental Adaptability - Hwang Kim; Doo-Hyung Lee; Sun-Hee Hong; Jong-Seok Park; Jung-Wook Kho; Young-Joong Kim (Diversity)
This study investigates the reintroduction and ecological adaptation of the endangered dung beetle, Gymnopleurus mopsus, in South Korea, a region from which it has been absent since the 1970s. To facilitate this, we imported genetically identical populations of G. mopsus from Mongolia and embarked on a comprehensive restoration research project. A key focus of this endeavor was to evaluate the adaptability of these beetles to the local environment, an essential aspect of successful reintegration of species from foreign ecosystems. Under meticulously controlled field cage conditions, we conducted an in-depth monitoring of the life history traits of G. mopsus. This monitoring revealed that the adult beetles, which entered hibernation in September 2019, began emerging in stages from late April to May 2020. Following hibernation, we observed that the adults engaged in reproductive activities from late-May until early-August, with the emergence of the first-generation (F1) adults occurring from late-July to mid-September. This led to a notable tripling in population size, increasing from 34 to 109 individuals. The successful survival and reproductive behaviors of these Mongolian dung beetles in the climatic conditions of Korea suggest a promising potential for their adaptation when reintroduced into native habitats. We are now directing our efforts towards long-term monitoring, focusing on the survival and reproductive efficacy of these new generations, to further validate the success of this ecological restoration project.